New analyses of worker well-being - Polachek, S. W.; Tatsiramos, Konstantinos (Emerald, 2013)
This volume contains new important research on worker well-being in a changing economy. Topics include employee compensation, human capital investment, womens wages, unemployment, and the effects of government policies. Among the questions answered are: Does free-trade (particularly regarding NAFTA) affect womens wages relative to mens? Can guaranteeing college scholarships raise high school students grade-point averages? Does increasing wage dispersion within a plant induce workers to put out more effort; or does it decrease commradery among employees, thereby lowering productivity? Does deferring worker pay really affect productivity on the job? Do firms manipulate fringe benefits (job characteristics) to adequately compensate workers for dangerous jobs? Do business cycles influence the terms of effort-enhancing labor contracts? How can workers signal their potential quality when displaced by plant closings? How severe are the detrimental effects of long-term joblessness? And finally, how do changes in welfare laws affect recipients time allocation at home?
Includes index.